Delotvorni programi tretmana za adolescente u sukobu sa zakonom i osvrt na Multisistemsku terapiju - Dovijanić, Sofija; Maljković, Marija (Specijalna edukacija i rehabilitacija, 2025)
Introduction. The ineffectiveness of some of the widespread interventions for juvenile offenders, alongside the deleterious consequences of youth violence, underscores the need for professionals to rely on scientifically proven interventions in working with these youth. Aims. The present review highlights the importance of evidence-based practice in treating juvenile offenders. We also explored the current situation in Serbia, offering a critical perspective on existing treatment practices, but also recommendations for decision-makers, researchers, and practitioners. Methods. The results of systematic literature reviews and other studies in this field were analyzed and narratively systematized. Results. Research consistently points to multimodal approaches and family therapy as the most effective options, while commonly advocated for methods such as diversion, educational programs, restorative justice, scare tactics, and intensive probation often fail to achieve behavioral change. Multisystemic therapy stands out as one of the most effective and well-documented models. Conclusion. Strengthening the link between science and practice, through adherence to evidence-based principles and the establishment of a transparent system for monitoring treatment process and effects, is emphasized as essential.